Marketing digital na pandemia - CARVALHO, Carlos Manoel Vitor de; SILVA, Julya Teixeira da (060, 2022)
No trabalho proposto, iremos apresentar o problema que, não só impactou o mundo, mas também o mercado, que é o principal para manter a economia do país. O objetivo é mostrar as soluções, os métodos e técnicas, que foram abordadas pelas empresas. Baseado em pesquisas em sites e com quem já atua nesta área. Lembrando que o marketing Digital existe há anos, mas foi na Pandemia que o Mercado Digital cresceu. O Marketing é o coração do negócio.

In the proposed work, we will present the problem that not only impacted the world, but also the market, which is the main thing to maintain the country's economy. The objective is to show the solutions, methods and techniques that were approached by the companies. Based on research on websites and with those who already work in this area. Remembering that Digital marketing has been around for years, but it was in the Pandemic that the Digital Market grew. Marketing is the heart of the business.
Digital marketing in the pandemic
Keywords: Administração; Marketing; Gestão e Negócios